The book of giving : poems of thanks, praise, and celebration (New York : Dutton Children's Book, 1995)
A collection of poems celebrating the act of giving and the joy of receiving.
Keywords: Generosity--Juvenile poetry; Children's poetry, American; Children's poetry, English; Gratitude--Juvenile poetry; Praise--Juvenile poetry